ความสัมพันธ์เชิงอำนาจระหว่างผู้นำศาสนากับผู้นำการเมืองท้องถิ่น - (เจติยะ), พระมหามนัส ปญฺญาวุฑฺโฒ; (เสนศรี), พระมหาฉัตรเพชร สุภทฺโท; โทอื้น, วรเชษฐ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This academic article aims to reflect on the issue of the “power relationship between religious leaders and local political leaders.” It seeks to examine how these two groups are connected in terms of power, roles, and influence within community-level society. The study focuses on understanding how religious leaders and local political leaders are linked to one another and mutually reinforce each other’s interests, including in matters of belief, social values, political decision-making processes, and the setting of directions for local development. The research adopts Michel Foucault’s concept of “relational power” and Pierre Bourdieu’s concept of “social capital” as analytical frameworks to explain the mechanisms through which such relationships are formed, maintained, and negotiated, as well as how influence is exchanged between the two groups. A review of the relevant literature indicates that the relationship between religious leaders and local political leaders is not best understood as a rigid hierarchy of superiors and subordinates, nor as a situation in which one side unilaterally dominates the other. Rather, it is characterized by multiple forms of interdependence, mutual support, and ongoing negotiation. Religious leaders possess moral authority and enjoy public faith and respect; consequently, they play a significant role in enhancing the legitimacy of local political leaders. At the same time, local political leaders often support religious activities by providing budgets, resources, and venues, and by promoting public policies that benefit religious institutions. This, in turn, generates a reciprocal exchange of power and shared interests, enabling both sides to sustain their status and roles within the local arena. Accordingly, the relationship between religion and politics at the local level should be understood as a dynamic that is complex and contingent upon social and cultural contexts as well as the particular conditions of each historical period. A clearer understanding of this power relationship not only helps illuminate Thai local governance more comprehensively, but also highlights Thailand’s political culture, which remains closely intertwined with religion as a key source of meaning and legitimacy for power at the community level.